![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
a)
$8^3:(-8)^{-5}=8^3.(-8)^5=8^3.(-8^5)=-8^3.8^5=-8^{3+5}=-8^{13}$
b)
$x^3y^4:(x^3y)=x^{3-3}.y^{4-1}=x^0.y^3=y^3$
c)
$5x^2y^4:(10x^2y)=(5:10).(x^2:x^2)(y^4:y)=\frac{1}{2}.1.y^3=\frac{1}{2}y^3$
d)
$\frac{3}{4}(xy)^3:(\frac{-1}{2}x^2y^2)$
$=(\frac{3}{4}: \frac{-1}{2})(x^3:x^2).(y^3:y^2)$
$=\frac{-3}{2}xy$
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{7\left(x-y\right)^5-5\left(x-y\right)^4+3\left(x-y\right)^3+2\left(x-y\right)^2}{y-x}\)
\(=-7\left(y-x\right)^4-5\left(y-x\right)^3-3\left(x-y\right)^2+2\left(y-x\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Chỉ khi x + y + z = 0 mới như vậy.
Cụ thể :
Ta có :
\(x^3+y^3+z^3-3xyz\)
\(=\left(x+y\right)^3+z^3-3xy^2-3x^2y-3xyz\)
\(=\left(x+y+z\right)\left[\left(x+y\right)^2+z^2-\left(x+y\right)z\right]-3xy\left(x+y+z\right)\)
\(=\left(x+y+z\right)\left[x^2+y^2+2xy+z^2-xz-yz-3xy\right]\)
\(=0\) là BS xyz
= 1 nha a